Characteristics of Newly Diagnosed Type 2 Diabetes in Chinese Older Adults: A National Prospective Cohort Study - Fang Lv; Xiaoling Cai; Dayi Hu; Changyu Pan; Danyi Zhang; Jie Xu; Linong Ji (Journal of Diabetes Research)
Aim. To investigate the metabolic profiles of newly diagnosed type 2 diabetes (NEW2D) in Chinese older adults (≥65 years) and assess the proportion of patients who achieved the targeted goals of blood glucose, blood pressure, and blood lipid. Methods. NEW2D study was an observational, longitudinal, prospective cohort study involving patients who were diagnosed with type 2 diabetes (T2D) within the past 6 months and had a follow-up of 12 months. Participants were divided into younger NEW2D group (aged 20-65 years old) and older NEW2D group (aged ≥65 years old) according to age of diabetes onset. The baseline metabolic profiles were compared and the proportion of patients achieving adequate control of blood glucose, blood pressure, and blood lipids in reference to target goals were assessed during treatment. Results. The older NEW2D (n=1362) had a lower BMI, HbA1c%, diastolic blood pressure, triglyceride, low-density lipoprotein cholesterol (LDL-C), and total cholesterol, higher systolic blood pressure, and high-density lipoprotein cholesterol levels at baseline. 47.8%, 66.7%, and 39.4% reached the target of HbA1c<7.0%, BP<140/90 mmHg, and LDL−C<2.6 mmol/L, respectively. After 12 months, the proportion achieving above three targets increased to 70.2%, 76.1%, and 47.5%, respectively. The proportions of patients achieving three combined therapeutic targets doubled from 13.5% to 26.7%. Conclusion. The older NEW2D patients have special metabolic profiles compared with younger patients. The control of cardiovascular disease risk factors was suboptimal in older adults with type 2 diabetes.